Peran Influencer Dalam Meningkatkan Brand Awareness Melalui Instagram Stories - Mubarok, Zacky; Andi Azhar (PT. Karya Inovatif Nusantara, 2025)
Influencers are such a modern phenomenon that there has been a huge increase in their collaborations with marketing agencies over the past year. The majority of influencers fall into the following categories: celebrities, industry experts and thought leaders, bloggers or content creators and micro-influencers. In the current era of industrial revolution 4.0, promotional strategies must be able to take advantage of existing opportunities, they must be able to utilize social media as a marketing tool. This research aims to analyze the influence of the role of influencers in increasing brand awareness through Instagram stories. This research uses qualitative research which analyzes the influencer phenomenon which is often used by companies for promotions. The approach method uses a literature review and the flow used is the AISAS approach model (Attention, Interest, Search, Action and Share). This research found that by utilizing the social media Instagram, which has many supporting features, information can be done quickly and on target. Influencers often become brand ambassadors for products that have high credibility due to the influence of their followers.